Contamination of a hospital plumbing system by persister cells of a copper-tolerant high-risk clone of Pseudomonas aeruginosa. (15th June 2019) - Jeanvoine, Audrey; Meunier, Alexandre; Puja, Hélène; Bertrand, Xavier; Valot, Benoît; Hocquet, Didier
Abstract: Background: Pseudomonas aeruginosa (PA) is an important opportunistic pathogen that thrives best in the distal elements of plumbing and waste-water systems. Although nosocomial outbreaks of PA have been associated with water sources, the role of the plumbing system of healthcare premises as a reservoir for this pathogen is still unclear. Materials and methods: We collected water samples from 12 technical areas, distant from any medical activity, in a teaching hospital in France once a week for 11 weeks. We used a method that resuscitates persister cells because of the nutrient-poor conditions and the presence of inhibitors ( e.g. chlorine and copper ions). Briefly, water was sampled in sterile bottles containing 100 μM of the copper-ion chelating agent diethyldithiocarbamate (DDTC). A portion of the samples was immediately filtered through 0.45-μm membranes, deposited on R2A agar plates, and incubated seven days at 22 °C (following European recommendations). The remaining water was incubated 14 days at 22 °C and then filtered and cultured on R2A, blood-, or cetrimide-containing agar plates. PA isolates were identified by MS MALDI-TOF, genotyped by PFGE and WGS, and tested for survival in a 150 μg/L copper (II) sulphate solution. Results: Although the 12 water sampling points always tested negative with the recommended method, 67% were positive at least once for PA with the adapted method ( i.e. with DDTC). The 14 PA persister isolates found throughout the plumbing system were clonal and belong to the high-risk clone ST308. Their genome harbours a 37-kb genomic island (GI-7) containing 13 genes linked to copper resistance. ST308 survived better in the copper solution than comparators that did not harbour GI-7 ( P. aeruginosa strains PAO1, PA14, and ST235). The deletion of GI-7 in ST308 abrogated its tolerance to copper. The GI-7 nucleotide sequence shares 98% and 72% identity with sequences from the environmental species Pseudomonas putida and the phytopathogenic species Pseudomonas syringae, respectively. Conclusion: We report the contamination of the plumbing system of a healthcare premises by persister cells of the high-risk clone P. aeruginosa ST308. New recommendations for the monitoring of water contamination should consider persister cells. The genomic island GI-7, which confers tolerance to copper, probably originates from Pseudomonas species found in copper-contaminated soils and plants. Agricultural practices may have an unexpected consequence, allowing copper-tolerant pathogens to survive in the hospital environment and contaminate fragile patients. Graphical abstract: Image 1 Highlights: The water network of a hospital is colonized by P. aeruginosa ST308 high-risk clone. The pathogen exclusively forms persisters undetected by recommended techniques. P. aeruginosa ST308 is tolerant to copper due to a genomic island GI-7. GI-7 probably originates from soil- and plant-associated Pseudomonas .